2022
DOI: 10.3991/ijim.v16i02.27677
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing HOTS using Problem-Based Learning and Digital Game in the Context of Malaysian Primary School

Abstract: Learning in the 21st century emphasize on development of higher order thinking skills such as problem-solving skills with substantial highlight was given toward student-centred approach. Digital game and problem-solving activities are an ideal combination of student-centred approach which facilitate active participation for students to practice and develop their thinking skills. This study was conducted to investigate the effect and the process of using digital game and problem-based learning skills to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…The teaching media, learning situations, or learning environment will greatly determine students' decisionmaking skills, especially in science material. This is in line with Tong et al (2022), who stated that the learning environment dramatically influences students' decision-making skills in the learning process.…”
Section: Resultssupporting
confidence: 88%
“…The teaching media, learning situations, or learning environment will greatly determine students' decisionmaking skills, especially in science material. This is in line with Tong et al (2022), who stated that the learning environment dramatically influences students' decision-making skills in the learning process.…”
Section: Resultssupporting
confidence: 88%
“…The discourse surrounding the implementation of game-based learning in middle schools has shed light on the potential advantages of integrating gaming components into the academic curriculum (Tong et al, 2022;Gao et al, 2020). Research has demonstrated that game-based learning can enhance student engagement, motivation, and knowledge retention by providing interactive and immersive learning experiences that cater to a variety of learning styles (Noroozi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Future studies are recommended to examine the chances for sustainable growth in the 3D animation content creation industry via the lens of virtual reality and gaming. The aspects of gaming [34], problem-based learning and digital games [35], and game-based learning kits with the integration of augmented reality [36] are also worth consideration in future research. By identifying developing patterns in the field and comparing them to earlier research on the subject of 3D animation, this study serves as a reference for future research.…”
Section: Discussionmentioning
confidence: 99%